Upaya Kepala Sekolah dalam Meningkatkan Manajemen Mutu Pendidikan Sekolah Dasar - Metriana Kamlasi; Mety Maria Enjela Neolaka; Quin Elisabeth Dima; Angita Ever Yismaya Sae; Yanti Y. E Sole (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The calibre of education in schools is significantly influenced by the efficacy of management methods, with the principle acting as a pivotal leader in guiding and orchestrating school operations. This research aims to investigate the tactics used by principals to improve educational quality in elementary schools. Using a qualitative research design with a literature review approach, the study highlights the principal’s responsibilities as an educator, manager, administrator, innovator, and motivator in supporting school improvement. The results reveal that major challenges faced by primary schools include inadequate facilities and infrastructure, as well as insufficient teacher competence. To address these issues, principals implement various initiatives, such as strengthening teacher capacity, improving educational facilities, and fostering collaboration with relevant stakeholders. The study underscores the crucial role of principal leadership in harmonizing all school components to achieve higher standards of educational quality.